Utilization of WebGIS for Visualization of the Distribution of Tourist Destination Religious Objects in Nagari Batuhampar of Lima Puluh Kota Regency, West Sumatera Province - Susetyo, Bigharta Bekti; Purwaningsih, Endah; Sutriani, Widia; Purnamasari, Eva; Bagus, Muhamad Ikhwan (Society of Visual Informatics, 2024)
Nagari Batuhampar has several tourist attractions planned as object tourist destinations in the strategic plan. However, publication and presentation on social media are less effective in promoting the unique characteristics of tourist attractions. This research aims to identify the distribution of tourist destination objects in Nagari Batuhampar, followed by comprehensive information. The type of research used is descriptive survey research with the waterfall method, which consists of requirement analysis, system analysis, system implementation, system testing, system evaluation, operation, and maintenance. Data collecting techniques include observation using GPS and documentation, interviews to obtain information for web development, and questionnaires. Furthermore, the built-in data application QGIS 3.32.3” Lima” is open source. WebGIS, built using the Database Management System (DBMS) approach, is designed as software to manage big data. Big data is meant to be a collection of lots of data tailored to the project being carried out, such as mapping the distribution of public facilities and village potential. In this research, DBMS focuses on spatial data and religious and supporting tourism attributes. This is focused on data on religious and supporting tourism attributes. The result found that historical religious tourist attractions dominated the distribution of attractions in Nagari Batuhampar. The WebGIS of Tourist Destination Object was constructed using a waterfall method that was effectively created. This development was conducted through system evaluation tests, resulting in most respondents being satisfied with the process's performance.